Contemporary studies of risks in emerging technology - Grima, Simon; Sood, Kiran; Özen, Ercan (Emerald studies in finance, insurance, and risk management ;, 2023)
With the rapid development of technologies, it becomes increasingly important for us to remain up-to-date on new and emerging technologies. This series, therefore, aims to deliver content on current and future technologies and how the young generation benefits from this. The global financial crisis has highlighted major weaknesses in financial records, information, and data. These weaknesses have led to inadequacies in the access to financial records and information, higher operational risks, flawed bankruptcies, and foreclosure proceedings. The Lockdown due to the ongoing pandemic COVID-19 has increased the scope for criminals to exploit vulnerabilities and commit financial crimes. The increased online presence and homeworking have significantly expanded the attack surface for cybercriminals. Criminals are exploiting vulnerabilities, increasing the risks of cyber-attacks, money laundering and terrorist financing. Research is therefore needed to identify trends, tools and applications that will provide the needed records, information, and data to support more effective financial analysis and risk management. Financial Technology (FinTech) has become one of the most pioneering and cost-effective disruptive technologies. Initial adaptation of FinTech solutions has permitted several start-ups, financial service providers, and other assorted sectors to accomplish an augmented pace of growth. Contemporary Studies of Risks in Emerging Technology: Part A also highlights how emerging technologies are altering the subtleties of doing business for financial services benefactors, possibility of emerging technologies, advantages and disadvantages, technology linked issues/challenges in financial services, and also highlights drivers of this revolution.